IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 32 TAHUN 1999 PASAL 19 AYAT (1) TENTANG SYARAT TATA CARA PELAKSANAAN HAK WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS II A SAMARINDA - Dharmawan, Yusuf (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
Â AbstractThe rights of prisoners as Indonesian citizens who lost their independence for committing a crime should be done in accordance with human rights. Often found in Correctional Institutions that the rights of prisoners have not been given according to their rights as citizens. Based on the description of the right of Citizens Penas Penasanan in terms of getting a decent nutritious food for health and stamina body, good quality, cooked and presented wellThis type of research is empirical legal research with an approach using descriptive, statutory and conceptual properties. Using primary, secondary and non-legal sources of legal material. then the legal material is processed in a deductive way and then draws it into a more specific conclusion and is arranged systematically. Results from research that a). Implementation of Fulfillment of the right to get food in Class II Penitentiary A Samarinda not good enough. Based on Law No. 12 of 1995 and Government Regulation No. 32 of 1999, b). Factors that hamper efforts to fulfill the right to get food are Lack of adequate facilities in the kitchen of the Class II A Correctional Institution in Samarinda, Lack of officers / staff of LAPAS officers , and the unavailability of chefs (cooks) and nutritionists. c). The role of the Samarinda Class II A LAPAS Responsibility has been carried out in accordance with the existing program procedures in prison but not fully done due to constraint factors such as over capacity of LAPAS, absence of nutritionists and chefs, and supporting equipment in terms of food fulfillment for inmate.The internal efforts made by the prison such as farming, honing skills, sports, and formal and non-formal education and external efforts, namely by establishing cooperation between the Regional Government and the private sector with the aim of improving infrastructure and earning correctional assistance and LAPAS by implementing various programs proclaimed by the Central Government according to the real condition in LAPAS